Psychiatric disorders in patients with benign and malignant sinonasal tumors: a prospective cross-sectional study - Guang-Ye Zhan; Guang-Ye Zhan; Guang-Ye Zhan; Hui-Fang Wang; Dong-Fang Wang; Yi-Hui Wen; Yi-Hui Wen; Hua Zhong; Hua Zhong; Wei-Ping Wen; Wei-Ping Wen; Jian Li; et al. (Frontiers in Psychology)
ObjectiveTo assess the prevalence of depression, anxiety, insomnia, and somatic symptom disorder (SSD) in patients with benign and malignant sinonasal tumors.Materials and methodsPretreatment patients with sinonasal tumors were prospectively recruited on the rhinology ward of a tertiary hospital from July 2021 to March 2022. The electronic questionnaire which contains the rhinological symptom scale, the 22-item Sinonasal Outcome Test (SNOT-22) Scale, the Patient Health Questionnaire-9 (PHQ-9), the Generalized Anxiety Disorder-7 (GAD-7), the Insomnia Severity Index (ISI), and the Patient Health Questionnaire-15 (PHQ-15) was filled out by patients at admission. The associations between the scores of symptom/SNOT-22 and psychometric tests were assessed by the Pearson correlation coefficient (r) and simple linear regression. The receiver operating characteristic (ROC) analysis was used to evaluate the performance of the SNOT-22 score in predicting psychiatric disorders.ResultsThirteen patients with benign sinonasal tumors and 15 patients with malignant sinonasal tumors were recruited. The benign and malignant groups did not differ significantly regarding symptomatology and mental wellbeing. Of the total patients, 9 were at risk of depression (PHQ-9 > 4), 10 were at risk of anxiety (GAD-7 > 4), 11 were at risk of insomnia (ISI > 7), and 11 were at risk of SSD (PHQ-15 > 4). The overall symptom, facial pain/pressure, postnasal drip, and SNOT-22 scores were positively associated with scores of psychometric tests. Patients with a high SNOT-22 score (>18) are likely to be affected by comorbid psychiatric disorders. When interpreting the results of this study, it should be noted that screening tools, not diagnostic tools, were used to identify psychiatric risk.ConclusionDepression, anxiety, insomnia, and SSD are prevalent in patients with sinonasal tumors. Otolaryngologists should have a low threshold to ask the patient about psychiatric symptoms, especially for patients with an SNOT-22 score > 18.